Impacts of bottom fishing on the sediment infaunal community and biogeochemistry of cohesive and non‐cohesive sediments. (29th June 2016) - Sciberras, Marija; Parker, Ruth; Powell, Claire; Robertson, Craig; Kröger, Silke; Bolam, Stefan; Geert Hiddink, Jan
Abstract: Bottom‐trawl fisheries are wide‐spread and have large effects on benthic ecosystems.We investigate the effect of scallop dredging on sand and otter trawling on mud by measuring changes in the infaunal community and the biogeochemical processes which they mediate. We hypothesize that changes in biogeochemistry due to fishing will be larger in mud where macrofauna‐mediated processes are expected to play a greater role, than in sand where hydrodynamics mediate the redox system. We sampled benthic infauna, sediment pore‐water nutrients, oxygen, chlorophyll a (Chl a ), apparent redox potential discontinuity layer, organic carbon and nitrogen content over a gradient of fishing intensity in sand and mud. The effects of fishing on biogeochemistry were stronger on mud than on sand, where biogeochemistry appeared to be more strongly influenced by tidal currents and waves. On mud, trawling increased sediment‐surface Chl a and ammonium concentration beyond 5 cm depth, but decreased ammonium and silicate concentration in the upper sediment layers. The effects of fauna and bioturbation potential on biogeochemistry were very limited in both mud and sand habitats. Our results suggests that otter trawling may be affecting organic‐matter remineralization and nutrient cycling through sediment resuspension and burial of organic matter to depth rather than through the loss of bioturbation potential of the benthic community. In conclusion, our hypothesis that the effects of trawling on biogeochemistry are larger in mud is supported, but the hypothesis that these effects are mediated by changes in the infauna is not supported. These results imply that management of trawling on muddy sediments should have higher priority.